Tooth extraction in patients taking nonvitamin K antagonist oral anticoagulants - Yoshinari Morimoto; Chizuko Yokoe; Yuko Imai; Megumi Sugihara; Toshiko Futatsuki (Elsevier, 2016)
Background/purpose: The nonvitamin K antagonist oral anticoagulants direct-thrombin inhibitor dabigatran and the Xa inhibitors rivaroxaban and apixaban are now being used clinically. The course of the patients on these anticoagulants who underwent tooth extraction was assessed. Materials and methods: The medical charts of these patients were investigated. Tooth extraction was performed while maintaining conventional anticoagulant therapy. Results: Twenty-three teeth were extracted in 19 patients, including two surgical extractions. Among the 19 patients, nine patients ingested rivaroxaban, six apixaban, and four dabigatran. One patient on rivaroxaban showed persistent postoperative bleeding following two surgical extractions. Mild oozing was observed in five patients (two on rivaroxaban and three on apixaban). There was no bleeding episode in the patients on dabigatran. Conclusion: The patients on rivaroxaban with a prolonged prothrombin time value have a higher risk of bleeding, especially undergoing surgical extraction. Apixaban correlates to neither activated partial thromboplastin time nor prothrombin time values and the countermeasures should be employed based on the clinical findings.